INFLUENCE OF FORMAL SMALL INDUSTRY PRODUCTION AND REVENUE REALIZATION TAX ON ECONOMIC GROWTH IN ACEH UTARA DISTRICT - Sarah Fernanda; Ichsan Ichsan (Journal of Malikussaleh Public Economics, 2021)
This study aims to determine the effect of Formal Small Industrial Production and Realization of Tax Revenues on Economic Growth in North Aceh Regency. The datta used in thits studyy are time series in the period e2010-2017. The analytical model used iin this studyy is the Multiplle Linear Regressions Model. The resullt showeld that are that togetther with the variiablles of formal smaall industriasl productiont and the realizations of tax revenuese had a significants effect on economicc growth. While partialy the formall small industriasl productions is significanst and positivee effect economicc growth and the realizations of tax revenuess are significanst and negativelyy effect economicc growth in the districts of North Aceh.